Recovery of mechanical detection thresholds after direct digital nerve repair versus conduit implantation. (September 2017) - Huber, J. L.; Maier, C.; Mainka, T.; Mannil, L.; Vollert, J.; Homann, H.-H.
The purpose of this study was to assess sensory and functional nerve recovery after digital nerve injury in patients with an end-to-end suture (S) or with implantation of a collagen conduit (C) to bridge a nerve gap. Fifteen S and 11 C with a follow-up of 6–36 months and 28 healthy control participants were enrolled. Methods of assessments were quantitative sensory testing, the Disabilities of the Arm, Shoulder and Hand questionnaire (DASH), range of motion and the painDetect questionnaire. After both procedures, sensory profiles showed largely recovered function of C and Aδ fibres but severe loss of Aβ-fibre function leading to increased mechanical detection thresholds. There was only minimal allodynia. Severe pain was absent. Patients with conduits reported more functional impairment, especially in work performance, which correlated with the assessed loss of Aß-fibre function. Level of evidence: III